The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acsami.0c14772
|View full text |Cite
|
Sign up to set email alerts
|

Capture and Release Recyclable Dimethylaminomethyl-Calixarene Functional Cloths for Point-of-Use Removal of Highly Toxic Chromium Water Pollutants

Abstract: Chromium(VI) contamination of drinking water arises from industrial activity wherever there is a lack of environmental legislation enforcement regarding the removal of such pollutants. Whilst it is possible to remove such harmful metal ions from drinking water through large scale facilities, there currently exists no safe and simple way to filter chromium(VI) oxoanions at point-of-use (which is potentially safer and necessary in remote locations or humanitarian scenarios). High surface area cloth substrates ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…42 Using this strategy, Badyal et al developed a multistage procedure for creating a composite material from PP fabric via pulsed plasma coating with poly(vinylbenzyl chloride), followed by covalent grafting of calixarene (Table 4(4)). 312 The prepared membrane is able to selectively entrap Cr 6+ oxoanions, making it attractive for point-of-use application in geographic regions lacking appropriate wastewater treatment plants or flawed environmental monitoring systems. Independently, PP fabric has been coated with electroconductive polyaniline (PANI) for adsorbing humic acid (Table 4(1)).…”
Section: Overview Of the Functional Upcycling Strategy For Different ...mentioning
confidence: 99%
See 3 more Smart Citations
“…42 Using this strategy, Badyal et al developed a multistage procedure for creating a composite material from PP fabric via pulsed plasma coating with poly(vinylbenzyl chloride), followed by covalent grafting of calixarene (Table 4(4)). 312 The prepared membrane is able to selectively entrap Cr 6+ oxoanions, making it attractive for point-of-use application in geographic regions lacking appropriate wastewater treatment plants or flawed environmental monitoring systems. Independently, PP fabric has been coated with electroconductive polyaniline (PANI) for adsorbing humic acid (Table 4(1)).…”
Section: Overview Of the Functional Upcycling Strategy For Different ...mentioning
confidence: 99%
“…326,327 Despite the simplicity and convenience of noncovalent approaches, the leakage of active components to the surrounding media limits their widespread application, which can be resolved via covalent modification. Thus, the sulfonation of PP in concentrated sulfuric acid has been implemented to improve [307][308][309] (c) heteroradicals functionalisation; 167,310 (d) sulfonation; 311 (e) grafting under physical treatment; 312,313 (f) oxidation; 42,314,315 (g) grafting of C-centered radicals; 316 and (h) diazirine modification through carbene intermediate. 317 This journal is © The Royal Society of Chemistry 2023 their thermal, 328,329 adsorption performance 330 or electrochemical properties 311 (Fig.…”
Section: Polypropylene (Pp)mentioning
confidence: 99%
See 2 more Smart Citations
“…[23][24][25][26][27][28] Therefore, the design of sensors for the detection of ions and biological molecules has attracted extensive attention. 29 It has been reported that rhodamine, 30,31 BODIPY, 32 calixarene, 33,34 cyclodextrin 35 and their derivatives can effectively identify metal ions, but it has not been found that they can perform secondary recognition for amino acids. It is well known that triazole compounds are used as corrosion inhibitors of organic copper, among which 1,2,4-triazole compounds are the most prominent.…”
Section: Introductionmentioning
confidence: 99%